Preconceito e esportes de aventura: A (não) presença feminina - Schwartz, G. M. [UNESP]; Figueiredo, J. P. [UNESP]; Pereira, L. M. [UNESP]; Christofoletti, D. A. [UNESP]; Dias, V. K. [UNESP] (Desafio Singular, Lda, 2013)
Participation in adventure sports have increased recently, perhaps because of its appealing and emotional aspects. Despite this overall increase, women's participation is restricted due to ingrained gender prejudice in society, however, there are some initiatives aimed at expanding women's participation in several adventure sports. In scientific literature there is a lack of studies on adventure sports, especially on gender issues, prejudice and female athletic performance. These aspects motivated this study, which aims to investigate from the female athletes' perspective; the prejudice and behaviors of male athletes when in their presence and the male athletes' acceptance of them. This exploratory research consists of a qualitative study developed through an open on-line questionnaire. This tool was posted on web logs and websites of sixteen well-known female Brazilian adventure sports athletes. The questionnaire answers were analyzed based on the Thematic Content Analysis Technique and indicate that, although most female athletes do not report the prejudice and rejection of men, these attitudes appear subliminally, deserving more attention in future studies. © FTCD/FIP-MOC.
Adventure sports and prejudice: The (no) female presence
Keywords: Adventure; Prejudice; Sport